2020
DOI: 10.3389/fbioe.2020.558996
|View full text |Cite
|
Sign up to set email alerts
|

The G-protein Coupled Receptor GPR8 Regulates Secondary Metabolism in Trichoderma reesei

Abstract: Changing environmental conditions are of utmost importance for regulation of secondary metabolism in fungi. Different environmental cues including the carbon source, light and the presence of a mating partner can lead to altered production of compounds. Thereby, the heterotrimeric G-protein pathway is of major importance for sensing and adjustment of gene regulation. Regulation of secondary metabolism is crucial in the biotechnological workhorse Trichoderma reesei for knowledge-based adjustment in industrial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…Three GPCRs (TRIREDRAFT_53238, TRIREDRAFT_58767, and TRIREDRAFT_62462) might be involved in RSR1 signaling because they showed signi cantly increased transcriptional levels in the rsr1 deletion strain (Table 4). A previous study reported that the TRIREDRAFT_53238 regulates secondary metabolism in T. reesei [50], indicating its regulatory role. Then, we used Δrsr1 as the starting strain to knockout tre62462, tre58767, and tre53238.…”
Section: Discussionmentioning
confidence: 96%
“…Three GPCRs (TRIREDRAFT_53238, TRIREDRAFT_58767, and TRIREDRAFT_62462) might be involved in RSR1 signaling because they showed signi cantly increased transcriptional levels in the rsr1 deletion strain (Table 4). A previous study reported that the TRIREDRAFT_53238 regulates secondary metabolism in T. reesei [50], indicating its regulatory role. Then, we used Δrsr1 as the starting strain to knockout tre62462, tre58767, and tre53238.…”
Section: Discussionmentioning
confidence: 96%
“…2 ). 74 Further experiments by Hinterdobler et al 75 revealed another layer of complexity of the tight control of T. reesei on secondary metabolism. Another gene in the vicinity of the sor cluster ( gpr 8), which encodes a class VII G-protein coupled receptor, was shown to have a considerable influence on the regulation of secondary metabolism in T. reesei in darkness.…”
Section: Challenges In Trichoderma Speciesmentioning
confidence: 99%
“…This light dependent regulation of secondary metabolism by GPR8 was found to be mediated in part by the TF YPR2 and the function of the FAD/FMN containing dehydrogenase gene (TrsorD). 75 Another challenge with linking Trichoderma secondary metabolites to their biosynthetic gene clusters is the intertwined and coordinated expression of different gene clusters. For example the disruption of T. hypoxylon tri5 gene which encodes the rst step in trichothecene biosynthesis, disrupted trichothecene biosynthesis as expected, but also resulted in the suppression of another biosynthetic pathway responsible for the production of tricinoloniol acids A-C 27-29 (Scheme 1).…”
Section: Challenges In Trichoderma Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascospore derived progeny were analyzed for the presence of gene deletion and mating type by PCR (Table S1). The functionality of the ham5 gene was con rmed by high resolution melt curve (HRM) analysis, performed as described previously 114 .…”
Section: Construction Of Recombinant Strainsmentioning
confidence: 99%